Systematic Development of Patient Decision Aids: An Update from the IPDAS Collaboration. (October 2021) - Witteman, Holly O.; Maki, Kristin G.; Vaisson, Gratianne; Finderup, Jeanette; Lewis, Krystina B.; Dahl Steffensen, Karina; Beaudoin, Caroline; Comeau, Sandrine; Volk, Robert J.
Background: The 2013 update of the evidence informing the quality dimensions behind the International Patient Decision Aid Standards (IPDAS) offered a model process for developers of patient decision aids. Objective: To summarize and update the evidence used to inform the systematic development of patient decision aids from the IPDAS Collaboration. Methods: To provide further details about design and development methods, we summarized findings from a subgroup ( n = 283 patient decision aid projects) in a recent systematic review of user involvement by Vaisson et al. Using a new measure of user-centeredness (UCD-11), we then rated the degree of user-centeredness reported in 66 articles describing patient decision aid development and citing the 2013 IPDAS update on systematic development. We contacted the 66 articles' authors to request their self-reports of UCD-11 items. Results: The 283 development processes varied substantially from minimal iteration cycles to more complex processes, with multiple iterations, needs assessments, and extensive involvement of end users. We summarized minimal, medium, and maximal processes from the data. Authors of 54 of 66 articles (82%) provided self-reported UCD-11 ratings. Self-reported scores were significantly higher than reviewer ratings (reviewers: mean [SD] = 6.45 [3.10]; authors: mean [SD] = 9.62 [1.16], P < 0.001). Conclusions: Decision aid developers have embraced principles of user-centered design in the development of patient decision aids while also underreporting aspects of user involvement in publications about their tools. Templates may reduce the need for extensive development, and new approaches for rapid development of aids have been proposed when a more detailed approach is not feasible. We provide empirically derived benchmark processes and a reporting checklist to support developers in more fully describing their development processes. Highlights Users of patient decision aids deserve assurance that the processes used to create these tools follow acceptable standards. Since the last update of the International Patient Decision Aid Standards, principles of user-centered design have been widely adopted by developers. Developers consistently underreport the involvement of users when describing the development of decision aids. Templates and a checklist may help developers more fully report on the processes they use in creating these tools.